The Chief ExecutivesThe Chief Executives. BarmashIsadore. Philadelphia: Lippincott. 1978. 255 pp., $10.95. - Wren, Daniel A. (Academy of Management Review, 1980)
The article reviews the book ?The Chief Executives,? by Isadore Barmash.